Messages from Tahrir : Signs from Egypt's Revolution - Karima Khalil (Cairo : The American University in Cairo Press, 2011)
This book showcases the signs held by protestors inCairo's Tahrir Square during the peaceful revolution in Egypt during 2011.
Keywords: Revolutions -- Egypt -- 21st century; Egypt -- History -- Revolution, 2011 -- Pictorial works; Egypt -- History -- 1981-; Egypt -- History -- 21st century; Egypt -- Politics and government